A case of trichotillomania with binge eating disorder: combined with N-acetylcysteine synergistic therapy - Xudong Zhao; Shikai Wang; Xiujuan Hong; Shaojia Lu; Sufang Tang; Yue Shen; Ming Feng; Ping Guo; Yu Fang (Annals of General Psychiatry, 2021)
Abstract Background Obsessive–compulsive and related disorders (OCRDs) are a group of intractable and chronic mental disorders. Trichotillomania (TTM) is a common type of OCRDs characterized by repetitive hair pulling, driven by escalating tension before the action and during the attempts to resist it. Binge eating disorder (BED) is a common type of eating disorder characterized by recurrent compulsive episodes of binge eating. Both have common psychological processes (tension or impulsion) and pathological manifestations (out of control), but the pathological mechanisms are still unclear and the current clinical treatments are often unsatisfactory for these two disorders. Case presentation A 25-year-old woman with TTM comorbid BED came to our hospital for treatment. She had accepted systematic cognitive behavioral therapy (CBT) and also monotherapy or multidrug therapy with sertraline, fluvoxamine, bupropion, risperidone in full dosage and duration for 2 years, but all of them did not work. We treated this case with N-acetylcysteine (NAC) as a synergist on the basis of recent treatment (fluvoxamine 150 mg/day and bupropion 300 mg/day). The pathological hair plucking behavior and binge eating symptoms were both significantly and rapidly improved, and the follow-up in next 14 weeks showed that the effect was still maintained. Conclusion To our knowledge, this may be the first case report of using NAC as a synergist to treat TTM comorbid BED successfully, which suggest that these two disorders may have a common pathophysiological mechanism. Moreover, NAC can be one choice as a synergistic treatment for OCRDs.